A PBX1 transcriptional network controls dopaminergic neuron development and is impaired in Parkinson's disease - Villaescusa, J Carlos; Li, Bingsi; Toledo, Enrique M; Rivetti di Val Cervo, Pia; Yang, Shanzheng; Stott, Simon Rw; Kaiser, Karol; Islam, Saiful; Gyllborg, Daniel; Laguna-Goya, Rocio; Landreh, Michael; Lönnerberg, Peter; et al. (The EMBO journal, 2016)
Pre-B-cell leukemia homeobox (PBX) transcription factors are known to regulate organogenesis, but their molecular targets and function in midbrain dopaminergic neurons (mDAn) as well as their role in neurodegenerative diseases are unknown. Here, we show that PBX1 controls a novel transcriptional network required for mDAn specification and survival, which is sufficient to generate mDAn from human stem cells. Mechanistically, PBX1 plays a dual role in transcription by directly repressing or activating genes, such as Onecut2 to inhibit lateral fates during embryogenesis, Pitx3 to promote mDAn development, and Nfe2l1 to protect from oxidative stress. Notably, PBX1 and NFE2L1 levels are severely reduced in dopaminergic neurons of the substantia nigra of Parkinson's disease (PD) patients and decreased NFE2L1 levels increases damage by oxidative stress in human midbrain cells. Thus, our results reveal novel roles for PBX1 and its transcriptional network in mDAn development and PD, opening the door for new therapeutic interventions.
Keywords: DNA-Binding Proteins; Cell Differentiation; Dopaminergic Neurons; pre-B-buněčný leukemický transkripční faktor 1; dopaminergní neurony; Substantia Nigra; Proto-Oncogene Proteins; mesencephalon; dopaminergic differentiation; Pre-B-Cell Leukemia Transcription Factor 1; substantia nigra; genové regulační sítě; Gene Regulatory Networks; Parkinsonova nemoc; Humans; ChIP‐Seq; Parkinson Disease; protoonkogenní proteiny; DNA vazebné proteiny; buněčná diferenciace; dopamine; lidé; stem cells